2019
DOI: 10.1097/prs.0000000000005484
|View full text |Cite
|
Sign up to set email alerts
|

Myth-Busting the DIEP Flap and an Introduction to the Abdominal Perforator Exchange (APEX) Breast Reconstruction Technique: A Single-Surgeon Retrospective Review

Abstract: Supplemental Digital Content is available in the text. This and Related “Classic” Articles Appear on Prsjournal.com for Journal Club Discussions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 64 publications
1
22
0
Order By: Relevance
“…As demonstrated by DellaCroce as well as in our current study, the risk of bulging or hernia is possibly lower than the conventional DIEP technique (DellaCroce et al, 2019). In our study, 41 patients have completed at least 1 year of follow‐up with no record of abdominal wall complications.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…As demonstrated by DellaCroce as well as in our current study, the risk of bulging or hernia is possibly lower than the conventional DIEP technique (DellaCroce et al, 2019). In our study, 41 patients have completed at least 1 year of follow‐up with no record of abdominal wall complications.…”
Section: Discussionsupporting
confidence: 77%
“…According to DellaCroce, pedicle engineering should be used when more than 1 cm of muscle or a motor nerve has to be sacrificed to allow flap elevation with multiple perforators (DellaCroce et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, several studies do not report which degree of muscle-sparing surgery they perform during MS fTRAM flap reconstruction. 9 , 13 , 14 , 23 , 26 , 27 As muscle-sparing flap harvest techniques become more popular and new variations are developed, 41 for the sake of accurate outcomes reporting and patient counseling, it is increasingly important for surgeons to adhere to a uniform classification system of muscle wall preservation. DellaCroce et al has expanded on the traditional classification system by offering a specific definition for the point at which muscle transection in the DIEP flap harvest equates to a muscle-sparing fTRAM flap.…”
Section: Discussionmentioning
confidence: 99%
“…More commonly, the reconstructive surgeon is faced with the decision to either limit the number of perforators, convert to muscle-sparing TRAMs or perform a pedicle disassembly. 10 When faced with such a challenge, we chose to cut the muscle along the tendinous intersection and we found that its substance can withstand repair, limiting the need to sacrifice muscle and avoiding a second micro-anastomosis.…”
Section: Discussionmentioning
confidence: 99%